O077 Explantation vs graft preserving strategy following primary endovascular aneurysm repair: two decades of EVAR and lessons learned. (22nd July 2022) - Sultan, S; Acharya, Y; Hynes, N
Abstract: Introduction: Continuous sac expansion could result in rupture, requiring aggressive management with reintervention to abolish the risk of rupture. Re-intervention could be achieved through salvage of the primary endograft through graft preserving strategy or explantation as necessary. We aimed to scrutinise our 20 years of EVAR practice, strategies indications for management and reinterventions following primary endovascular aneurysm repair (EVAR). Methods: We performed 1480 aortic interventions over the study period, including 910 EVARs. Using conventional and innovative diagnostic modalities with Prone contrASt enHanced computed tomography Angiography (PASHA), 133 endoleaks (ELs) were identified (15 type I, 98 type II; 18 type III; 5 type IV). Results: In total, 44 patients underwent re-intervention post-primary EVAR;18 EVAR GORE SalvAge Fabric Technique (ARAFAT), 12 double breastings, and 14 explantations. Mean EL detection duration following primary EVAR was 53.3 ± 6.82 months, while re-intervention time was 70.2 ± 6.98 months. Mean sac size before the primary EVAR and re-intervention were 6.00 and 7.51 cm. Polyester (61.40%) was the most commonly employed stent-graft material. Factors associated with the need for reintervention and the likelihood of chronic fabric fatigue failure (CFFF) included the use of more than three modular stent-graft components (3.42 ± 1.31); with the proximal stent-graft diameter of 31.6 ± 3.80 cm and the use of iliac limbs more than 18 mm. We had one peri-operative mortality following explantation due to sepsis-induced multiorgan failure. Conclusion: Increasing complications post-EVAR necessitates developing and studying reintervention strategies to salvage existing endograft and/or address graft-related complications. Take-home message: Increasing complications post-EVAR necessitates developing and studying re-intervention strategies to salvage existing endograft and/or address graft-related complications.